The effect of culture preservation techniques on patulin and citrinin production by Penicillium expansum Link - Santos, Isabel M. (2002)
Aims: To study the influence of culture preservation methods and culture conditions on the production of the mycotoxins patulin and citrinin by Penicillium expansum. Methods and results: Ten strains of Penicillium expansum were preserved using subculture and maintenance at 4 ºC, mineral oil, drying on silica gel and freeze-drying. Patulin and citrinin production was assessed on yeast extract sucrose agar (YES) and grape juice agar (GJ), using TLC before and after 0.5, 2–3, 6 and 12 months preservation. Citrinin was detected in all cultures for all preservation techniques on YES. The patulin profiles obtained differed with strain and culture media used. Conclusions: Citrinin production seems to be a stable character for the tested strains. There is a tendency for patulin detection with time apparently more consistent for silica gel storage and freeze-drying, especially when the strains are grown on GJ. Significance and Impact of the Study: Variability in the profiles of the mycotoxins tested seems to be more strain-specific than dependent on the preservation technique used.